PESISIR BERDAYA: Pemberdayaan Masyarakat Melalui Skrining, Edukasi, dan Pendampingan Self-Management Diabetes Melitus Berbasis Komunitas - Ceria Nurhayati; Nuh Huda; Christina Yuliastuti; Dedi Irawandi; Nur Muji Astuti; Imroatul Farida; Dul Majid; Sri Wahyu Wilujeng; Andan Peristika Didayana9 (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2026)
Diabetes mellitus (DM) is a non-communicable disease whose prevalence continues to increase, including in coastal communities with limited access to health services and information on disease management. Low awareness of early detection and the implementation of diabetes self-management has the potential to increase the risk of complications. Therefore, community-based community empowerment efforts are needed through screening, education, and ongoing mentoring. This community service activity aims to increase the knowledge, awareness, and ability of coastal communities to self-manage diabetes mellitus through a community-based health screening, education, and mentoring approach. The "PESISIR BERDAYA" program was implemented in 60 coastal community residents using a community-based participatory approach. Activities included risk factor screening and blood glucose level checks, providing education on diabetes mellitus and self-management, and mentoring through group discussions and health consultations. Evaluation was conducted by comparing participants' knowledge levels before and after education and identifying screening results to determine follow-up needs. A total of 60 participants participated in all series of activities with a high level of participation. The screening results indicated that some residents had risk factors and blood glucose levels above normal limits, requiring further monitoring at a health facility. Educational and mentoring activities can improve participants' understanding of risk factors, complication prevention, healthy eating patterns, physical activity, medication adherence, and the importance of regular blood glucose monitoring. A community-based approach also fosters social support and increases community motivation to adopt healthy lifestyles and self-manage diabetes.